INOVASI PEMBELAJARAN PPKN: EFEKTIVITAS MEDIA FLIPBOOK BERBASIS HEYZINE UNTUK MATERI BHINNEKA TUNGGAL IKA KELAS IV SD - Gde Oka Samahita; L. Heny Nirmayani; Putu Eka Sastrika Ayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to evaluate the effectiveness of using Heyzine-based digital flipbook media in enhancing students' cognitive understanding and affective engagement regarding "Bhinneka Tunggal Ika" (Unity in Diversity) in Pancasila and Civic Education (PPKN). Amidst 21st-century educational challenges, integrating innovative technology is essential to transform students from passive recipients into active participants. This research employs a mixed-methods approach with data triangulation techniques involving surveys, interviews, and classroom observations. Participants were selected using purposive sampling, encompassing educators across various levels to obtain a holistic perspective. The results indicate that flipbook integration significantly improves information retention and academic performance (evidenced by pre-test and post-test comparisons). Affectively, this media strengthens students' emotional connection to the values of diversity and tolerance through personalized, dynamic, and interactive learning experiences. However, the study also identifies challenges such as potential cognitive distraction, risks of excessive screen time, and systemic barriers related to digital access gaps. These findings underscore the importance of a blended learning approach that balances digital literacy with face-to-face social interaction. In conclusion, the synergy between substantial PPKN content and innovative technology not only optimizes learning outcomes but also creates an inclusive educational ecosystem that prepares students to become critical and adaptive global citizens.